Székelyföldi tudósítások ab TV
Youth Centre in Homoródszentmárton, Unitarian church, theatre performance, TV film based on novel “Ábel in the Woods” by Áron Tamási in Rumanian-Hungarian co production, music, landscapes, bookstore in Székelyudvarhely, Salvador Dali, Pentecost in Csiksomlyó, native American English language teachers in Székelyudvarhely,